Literature of Scotland and Slovenia: From Devolution to Post-devolution, from Socialism to Independence and Beyond - Luka Ličar (ELOPE, 2011)
This article looks at the situation of nationalism and literature in both Scotland and Slovenia in the 1980s and onward until the present day. In the case of Scotland the focus is on the devolution process and the literary renaissance which followed the failed referendum. The focus is also on the post-devolution literature and the challenges it faces both in terms of retrospect and the future challenges. In Slovenia in the 1980s the main points are the role of literature and culture in the process of democratisation and the reimagining of literature to reflect on the new situations. During this process comparisons as well as differences between both nations are revealed and some are specifically pointed out. Finally, there are certain concepts of how literature can advance and also hinder the development of a nation, which should be taken into consideration in the future developments.